Oxidative Stress in Aquatic Ecosystems 2011
DOI: 10.1002/9781444345988.ch1
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Stress in Tropical Marine Ecosystems

Abstract: he accumulation of oxygen in Earth's atmosphere has had profound effects on the geochemistry, physiology, and evolution of life on the planet. However, most organisms must also contend with the negative aspects of living in a world with oxygen. Reactive oxygen species (ROS) production is prevalent in the world's oceans and oxidative stress is an important component of the stress response in marine organisms exposed to a variety of environmental stressors such as thermal stress, which is now becoming more preva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
18
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 94 publications
2
18
0
Order By: Relevance
“…As such, ROS can have direct negative effects on intracellular parasites. ROS production occurs in Alexandrium during temperature increases (Jauzein & Erdner ) and has been observed in diverse marine organisms exposed to environmental abiotic stressors such as UV or heat shock (Lesser ); hence, it is considered an indicator of stress‐related pathways. Flores et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As such, ROS can have direct negative effects on intracellular parasites. ROS production occurs in Alexandrium during temperature increases (Jauzein & Erdner ) and has been observed in diverse marine organisms exposed to environmental abiotic stressors such as UV or heat shock (Lesser ); hence, it is considered an indicator of stress‐related pathways. Flores et al .…”
Section: Discussionmentioning
confidence: 99%
“…As such, ROS can have direct negative effects on intracellular parasites. ROS production occurs in Alexandrium during temperature increases (Jauzein & Erdner 2013) and has been observed in diverse marine organisms exposed to environmental abiotic stressors such as UV or heat shock (Lesser 2012); hence, it is considered an indicator of stress-related pathways. Flores et al (Flores et al 2012) found that the addition of ROS enzymes increased the survival of both the ciliate Tiarina fusus and the heterotrophic dinoflagellate Polykrikos kofoidii after exposure to Alexandrium, suggesting that ROS may be indirectly correlated to the toxicity of Alexandrium to protists.…”
Section: Functional Categorization Of Processes In Alexandriummentioning
confidence: 99%
“…In addition, we observed differential expression of several apoptosis-associated genes in both treatments, 7 and 22°C. Several studies demonstrated that sea urchins hold a complex apoptotic system (Agnello & Roccheri, 2010;Lesser, 2012). We found transcriptional changes at 7°C in apoptosis suppressor genes such as the Bcl2…”
Section: Discussionmentioning
confidence: 60%
“…invertebrates (see Lesser, 2012), and in genes containing death domains (downregulated: fas-associating death domain-containing protein and death ligand signal enhancer, Appendix S2) that induce cell apoptosis through the regulation of caspase activation (Agnello & Roccheri, 2010;Zhu et al, 2016). These findings suggest the activation of some particular pathways to control the programmed cell death at low temperatures.…”
Section: Discussionmentioning
confidence: 98%
“…These extreme conditions lead to ROS formation that may have deleterious effects on cell membranes causing lipid peroxidation (Collén and Davison , Kumar et al. , Lesser ). However, despite being continuously exposed to different biotic and abiotic stresses in their natural habitat, macroalgae maintain an intricate redox balance between lipid peroxidation and antioxidant defense system by accumulating antioxidants and up‐regulation of antioxidant enzymes (Matsukawa et al.…”
mentioning
confidence: 99%